Haemobartonellosis in a Domestic Cat in Indonesia: a Case Study - Satriawan, Ivan; Octaviani, Devi Intan Dyah Ayu (Veterinary Biomedical and Clinical Journal, 2021)
Haemobartonellosis is a disease caused by Haemobartonella felis or Mycoplasma haemofelis, which attacks red blood cells. Ctenocephalides felis could transmit Haemobartonellosis. Further, vertical transmission from mother to offspring and blood Â transfusion from infected animals could transfer the disease to other animals. This report aimed to describe the diagnosis and medical treatment of haemobartonellosis in a domestic cat in Indonesia. Physical examinations and blood analysis were carried out. The cat weighed 1,4 kg with 39,3Â°C temperature, CRT was three seconds, mucosa looked pale, and many Ctenocephalides felis fleas were found. The clinical symptoms detected were weakness, loss of appetite, and hair loss. A blood test indicated normocytic normochromic anemia. The rod-like formation within erythrocytes in blood smear was observed. Infection with Hemobartonella felis was diagnosed based on the blood test and the presence of numerous Ctenocephalides felis. Doxycycline was administrated at 10 mg/kg BW once a day for 21 days. The cat recovered clinically after 21 days, with a good appetite, normal mucosal color, and normal temperature